A preliminary study on local folktales exposures to support the development of animated courseware - Ibrahim, N. (Institute of Electrical and Electronics Engineers Inc., 2014)
Although Malaysia has a wide variety of folktales, children's knowledge about local folktales are less compared to foreign folktales. Until this moment, not much Malay folktales animation courseware was developed and published in the market, as well as the application for tablet. This paper discusses a preliminary study conducted for the research on developing an animation courseware for Malay folktales. In order to choose the genres to be developed for this courseware, a preliminary study has been carried out, which comprises of a survey using questionnaire distributed to 394 children aged from 9 to 11 years old assisted by their teachers. The results of this preliminary study showed that children are interested in animal, humour and exemplary stories. The results also proved that children are more familiar with foreign folktales compared to local folktales. Children preferred foreign folktales over local folktales because of the animation, graphic, character and colours presented in the story. Â© 2014 IEEE.